2005
DOI: 10.1086/427781
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Parasitological Characteristics of Puerperal Malaria

Abstract: Compared with nonpregnant women, puerperal women have a considerably increased risk for the development of malaria and/or parasitemia. This increased risk is caused both by the recurrence of P. falciparum parasitemia and by the increased susceptibility to new infections, although the latter plays a more significant role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
48
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 18 publications
(20 reference statements)
6
48
1
Order By: Relevance
“…In their study, Ramharter and others suggested that both mechanisms played a role, although most malaria cases were new infections acquired after delivery. 5 In our study, malaria cases were detected passively during the first six weeks after delivery. We reported a low rate of symptomatic malaria infections.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…In their study, Ramharter and others suggested that both mechanisms played a role, although most malaria cases were new infections acquired after delivery. 5 In our study, malaria cases were detected passively during the first six weeks after delivery. We reported a low rate of symptomatic malaria infections.…”
mentioning
confidence: 62%
“…4 Recently, two longitudinal studies found that women remained at high risk for malaria in the early postpartum period, as during pregnancy. 1,5 To investigate this issue, which may have important consequences for the management of women who recently delivered a child, we studied the immediate postpartum spontaneous evolution of malaria infections at delivery in pregnant women in Benin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, immunity to CSA-binding parasites and reduced risk of poor delivery outcomes have been associated in some studies (9,14,41) but not in others (4,6,11,39). Furthermore, the high incidence of malaria episodes observed a few weeks after delivery (8,15,34) suggests that other mechanisms may be also involved in the susceptibility of pregnant women to malaria.…”
Section: Sequestration Of Erythrocytes Infected By Mature Forms Ofmentioning
confidence: 99%
“…Similar genotyping approaches can be used to determine if malaria infections during the postpartum period are caused by new infections or rather by the same parasites that persist after delivery. However, to date only one study, based on a small number of isolates, has addressed this issue (34).…”
Section: Sequestration Of Erythrocytes Infected By Mature Forms Ofmentioning
confidence: 99%